Rancangan Teknis Tahap Penambangan Batubara Jangka Pendek Pada Pit X di PT Adimitra Baratama Nusantara, Kabupaten Kutai Kartanegara, Provinsi Kalimantan Timur - Safitri Tiara Wulandari Sukardi,; Partama Misdiyanta ,; Andy Erwin Wijaya, (ReTII, 2023)
Adimitra Baratama Nusantara is a mining company that carries out mining activities for coal excavated materials, which are carried out in the area of the IUP OP area owned by PT. Adimitra Baratama Nusantara itself, using the PT. Gunungmas Sukses Makmur (PT GSM). The mining system used is an open-pit mining system using the strip-mine method. Mining technical design is an important part of planning mining activities with the aim of achieving the desired production target and providing an overview of the planned mining progress over a period of time. Therefore, it is necessary to make a monthly mining technical plan. The average production target is 28,000 tons per month, and we carry out mining safely, effectively, and efficiently. The design will also determine the amount of digging and loading equipment needed each month. The method used in this study begins with data collection, both primary and secondary. The data obtained will then be processed using mining software to get the right mining pit design according to production targets. In addition, the data obtained is also processed using Microsoft Excel software to determine the amount needed for digging and loading equipment each month.